2020
DOI: 10.1017/s1478951520000863
|View full text |Cite
|
Sign up to set email alerts
|

The desire for death in Portuguese home-care palliative patients: Retrospective analysis of the prevalence and associated factors

Abstract: Objective Desire for death (DfD) is a complex and multifactorial dimension of end-of-life experience. We aimed to evaluate the prevalence of DfD and its associations, arising within the setting of a tertiary home-based palliative care (PC) unit. Method Retrospective analysis of all DfD entries registered in our anonymized database from October 2018 to April 2020. Results Of the 163 patients anonymously registered in our database, 122 met entry criteria; 52% were male, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…People faced with a diagnosis of advanced or late-stage cancer often experience existential-related distress, including hopelessness, demoralization, o desire for hastened death (1)(2)(3)(4) . Observational studies have found a prevalence of 13-18% of demoralization (5) , and up to 20.5% of desire for hastened death (6) during the late life stages of oncological patients. Authors such as David Kissane (7) and William Breitbart (4,8,9) have suggested that these experiences could represent a response to an existential crisis comprising a loss of meaning, values, and purpose in life.…”
Section: Introductionmentioning
confidence: 99%
“…People faced with a diagnosis of advanced or late-stage cancer often experience existential-related distress, including hopelessness, demoralization, o desire for hastened death (1)(2)(3)(4) . Observational studies have found a prevalence of 13-18% of demoralization (5) , and up to 20.5% of desire for hastened death (6) during the late life stages of oncological patients. Authors such as David Kissane (7) and William Breitbart (4,8,9) have suggested that these experiences could represent a response to an existential crisis comprising a loss of meaning, values, and purpose in life.…”
Section: Introductionmentioning
confidence: 99%
“…It asks how strongly these physical, cognitive, emotional, and social factors influence people to want to hasten their death, rather than how these factors can lead to further treatment planning and the prolongation of life. While incorporating more psycho-social questions, the QLIS recognizes the inseparability and impact on each other of physical, emotional, cognitive, and social factors that lead to wanting to hasten one’s death rather than trying to measure primarily emotional impact alone (Julião et al, 2020; Rosenfeld et al, 2000).…”
Section: Methodsmentioning
confidence: 99%